The Calculation of Erosion and Sedimentation Rate in Coastal Zone Using Satellite Imageries (Case Study: Kecamatan Muara Gembong, Kabupaten Bekasi, West Java) - Ekaputri, Dianlisa; Windupranata, Wiwin; Budi Harto, Agung (Indonesian Journal of Geospatial, 2014)
Abstract. Coastal zone is a transition area which always influenced by the changes of the land and ocean. The changes may occur due to the tide, current, wave, wind, sea water intrusion, runoff, contamination, or continental shelf area. As an effect, erosion and sedimentation phenomenon are occurred and could cause the changes of coastline shape. Kecamatan Muara Gembong which belongs to Kabupaten Bekasi is located in the Northern Coast of Java Island. Due to its geographical location, this area is threatened by the risk that is caused by erosion and sedimentation in the coastal zone. Therefore, study in this area is needed in order to identify the changes of the coastline. Coastline mapping through spatio-temporal LANDSAT-7 ETM+ satellite imageries is one of the methods to conduct this study. It uses satellite images from year 2000 â 2012. These images were processed by two visual image enhancement methods, named ratioing and BILKO algorithm, so that the visual differences between the land and the ocean could be identified. After the images were processed, coastline digitizing could be done annually from both methods. The result of this study is that there is a significant amount of erosion occurred in the coastal zone of Desa Pantai Bahagia and Desa Pantai Sederhana with the value of 139.05 Ha and 91.65 Ha from the ratioing method whereas the result from BILKO algorithm method is 141.56 Ha and 103.82 Ha. Desa Pantai Mekar has the least reduces, that is 30.44 Ha from ratioing method and 26.27 Ha from BILKO algorithm method. Based on Net Coastline Changes, the area of Kecamatan Muara Gembong from year 2000â2012 has reduced 346.54â349.56 Ha with the speed average of erosion that has been obtained is 28.88â29.13 Ha/year.Â Keywords: coastline changes, LANDSAT-7 ETM+ satellite imageries, erosion, sedimentation